Exploring Profitability of Compost Micro Enterprises in Chimaltenango, Guatemala: A Case Study of Business Sustainability for International Development - Timothy Silberg; Theresa Pesl Murphrey; Gary Wingenbach; Leonardo Lombardini (Journal of International Agricultural and Extension Education, 2013)
The economic sustainability of innovations disseminated to rural communities is an important issue in agricultural development. However, individuals working in international development often do not fully employ monitoring systems to analyze the long-term profit of an innovation prior to diffusion. This multi-case study used qualitative methods, including individual/group interviews and observations, to gather data to analyze all necessary inputs of compost microenterprises in Chimaltenango, Guatemala. Each micro-enterprise’s relative output was examined to determine how agricultural extension efforts could modify its operations to produce profits. The results revealed entrepreneurs lacked an awareness of total inputs used/needed for a compost operation and lacked effective financial record keeping practices. Net profit fell when inexpensive unskilled labor was used, when the operation’s infrastructure deterred access to transport or deterred vision of the operation and when entrepreneurs used greater quantities of free raw material to produce equivalent amounts of compost. All micro-enterprises were cognizant of their compost ingredient ratios, but none had quantified total materials used to produce given amounts for specific periods. Findings from this study provide insights into factors that impact profitability related to compost micro-enterprises in developing countries.
Keywords: Compost; Micro-Enterprise; Sustainability; Profit; Inputs; Guatemala